2022
DOI: 10.1007/s11573-022-01103-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and capital markets: the role of government responses

Abstract: This paper analyzes the moderation effect of government responses on the impact of the COVID-19 pandemic, proxied by the daily growth in COVID-19 cases and deaths, on the capital market, i.e., the S&P 500 firm’s daily returns. Using the Oxford COVID-19 Government Response Tracker, we monitor 16 daily indicators for government actions across the fields of containment and closure, economic support, and health for 180 countries in the period from January 1, 2020 to March 15, 2021. We find that government resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Recently, the world has experienced a new healthcare emergency as its impact has worsened and is more widespread than in the previous crises (Beer et al ., 2023). There still has been a great deal of lack of information and a huge amount of uncertainty regarding this crisis.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Recently, the world has experienced a new healthcare emergency as its impact has worsened and is more widespread than in the previous crises (Beer et al ., 2023). There still has been a great deal of lack of information and a huge amount of uncertainty regarding this crisis.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This increase in online trading is due to the restrictions on travel and work-from-home (Eliner, 2022) restrictions imposed in many countries; (5) Changing of Investment Patterns: Investors have also changed their investment patterns during the COVID-19 pandemic. Many have shifted from stocks and other high-risk assets to assets that are considered safer, such as government bonds and gold (Kumthakar & Nerlekar, 2020;Tanin et al, 2021); (6) Market Recovery: Despite the initial decline, the world's capital markets began to recover along with the slow economic recovery (Beer et al, 2023). Expectations of COVID-19 vaccine and government stimulus measures have given a boost to the capital market.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a study by the authors in Chang et al (2021) found that stock returns had a positive effect on the government responses to COVID-19 (the "lockdown" policy). Beer et al (2023), indicating that the responses of governments mitigate the negative stockmarket effect, while the authors in Scherf et al (2022) found that lockdown restrictions led to different reactions; there was a negative impact resulting from the increase in lockdown restrictions, but under-reaction during the lockdown announcement and then followed by overreaction. The authors in Cervantes et al (2022) suggested that changes in panic indexes because of the COVID-19 crisis had no significant relationship with raw stock-market returns.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies at the global level suggested different results; studies by the authors in Liu et al (2020), Uddin et al (2021), and Zhang et al (2020) suggested stock returns were negatively impacted; the authors in Uddin et al (2021) also suggested that resilience scores could significantly reduce the volatility of developed and emerging equity markets. Nonetheless, a study by the authors inChang et al (2021) found that stock returns had a positive effect on the government responses to COVID-19 (the "lockdown" policy) Beer et al (2023),. indicating that the responses of governments mitigate the negative stockmarket effect, while the authors inScherf et al (2022) found that lockdown restrictions led to different reactions; there was a negative impact resulting from the increase in lockdown restrictions, but under-reaction during the lockdown announcement and then followed by overreaction.…”
mentioning
confidence: 99%